The Dental Traits of Indonesian Javanese - Myrtati Dyah Artaria (Dental Anthropology Association, 2010)
This study describes the dental crown morphology of 91 Javanese of known sex and age, in Surabaya, East Java. The purpose was to explore the dental morphology in the area of East Java, especially in Surabaya. I scored a battery of three dozen dental traits on the permanent dentition (sexes pooled). Comparisons of the trait frequencies show that this Javanese sample does not exhibit a classic combination either of the Sinodont or Sundadont dental patterns. Instead, it represents some features of each, and this probably is due to the millennia of human migrations through this region.